BIOACTIVE COMPOUNDS IN BENGKOANG (Pachyrhizus erosus) AS ANTIOXIDANT AND TYROSINASE INHIBITING AGENTS - Endang Lukitaningsih (Indonesian Journal of Pharmacy, 2014)
In Indonesia, the roots of bengkoang (Phacyrhizus erosus) have been used as the excipient for sun screening and skin whitening paste. Since the active compounds exhibiting skin whitening or sun screening effect have not previously been studied, the aim of this study was to identify compounds with antioxidant and tyrosinase inhibitor activities. Soxhlet extraction was used as the method of isolation with petroleum ether as the solvent and it was followed by fractionation using ethyl acetate to obtain three isoflavonoids (i.e. daidzein (2); daidzein-7-O-ß-glucopyranose (3); 5-hydroxy-daidzein-7-O-ß-glucopyranose (4)), and a new pterocarpan (i. e. 8,9-furanyl-pterocarpan-3-ol (1)) which antioxidant activities (SC50% values) of 2.11; 11.86; 0.69 and 7.86 respectively. All compounds showed tyrosinase inhibiting activities with IC50 values of 4.38; 5.35; 7.49 and 22.20 mM, respectively for compound 4, 2, 1 and 3. These compounds can be used as antioxidant and skin whitening materials.